Catharanthus roseus: a natural source for the synthesis of silver nanoparticles - Mukunthan, KS (Asian Pacific Tropical Medicine Press, 2011)
OBJECTIVE: To develop a simple rapid procedure for bioreduction of silver nanoparticles (AgNPs) using aqueous leaves extracts of Catharanthus roseus (C. roseus). METHODS: Characterization were determined by using UV-Vis spectrophotometry, scanning electron microscopy (SEM), energy dispersive X-ray and X-ray diffraction. RESULTS: SEM showed the formation of silver nanoparticles with an average size of 67 nm to 48 nm. X-ray diffraction analysis showed that the particles were crystalline in nature with face centered cubic geometry. CONCLUSIONS: C. roseus demonstrates strong potential for synthesis of silver nanoparticles by rapid reduction of silver ions (Ag(+) to Ag(0)). This study provides evidence for developing large scale commercial production of value-added products for biomedical/nanotechnology-based industries.